Phytochemical composition and insecticidal activity of Acokanthera oblongifolia (Hochst.) Benth & Hook.f. ex B.D.Jacks. extract on life span and biological aspects of Spodoptera littoralis (Biosd.) - Khamis Wael; Al-Askar Abdulaziz; Kowalczewski Przemysław; Abdelkhalek Ahmed; Behiry Said (Open Agriculture)
Plant extracts with insecticidal properties are promising alternatives to conventional insecticides, which may pose risks to human health and the environment in pest management. In the current study, the methanolic extract of Acokanthera oblongifolia (Hochst.) Benth & Hook.f. ex B.D.Jacks. was characterized using high-performance liquid and gas-mass spectrometry chromatography. High-performance liquid chromatography analysis identified 14 polyphenols, the highest of which is chlorogenic acid (65637.79 µg/g), followed by naringenin and pyrocatechol at 2022.98 and 1509.11 µg/g, respectively. However, quercetin, gallic acid, ferulic acid, rutin, and kaempferol showed moderate quantities. The gas chromatography–mass spectrometry analysis identified the major polysaccharide, inositol (15.52%), followed by squalene and triterpene (11.02%) out of 35 polysaccharides. The major fatty acids, 11-octadecenoic acid, methyl ester, and methyl 9-cis, 11-trans-octadecadienoate, were 9.06 and 6.30%, respectively. The crude extract and chlorfluazuron 5% EC at LC15 were evaluated for the life table and biological aspects of S. littoralis (Boisd.) neonates after 48 h under laboratory conditions compared to the control. The toxicity of the LC15 at 48 h of chlorfluazuron 5% EC (0.31 mg/L) excelled the extract (178.95 mg/L) on the neonates. Life span tests showed that the larval longevity of the extract and chlorfluazuron colonies were 27.34 and 30 days, respectively. The control colony completed its life span at 38.66 days, whereas the extract colony ended at the pupae stage at 33.67 days. Biological aspects showed that the tested compounds decreased pupation percentages and weight. Pupae malformations caused by the extract (80.56%) outperformed chlorfluazuron (33.33%). The adult emergency decreased by the extract (0.33%), and no emergency was observed in chlorfluazuron colony. Ultimately, A. oblongifolia extract demonstrated significant life table elongations and developmental impairment, which may suggest potential and eco-friendly use for its prospective commercial preparations in controlling S. littoralis alternatively to chlorfluazuron 5% EC.